Changes of the Operating Costs during the Life Cycle in Existing Housing Stock. (June 2019) - Vytlačil, D
Abstract: The paper describes the dynamic model of the changes of the operating and investment costs that are associated with the energy consumption in the building. These costs are assessed for the building structure and HVAC systems. The aim of the research is to find the time dependent energy consumption and the cash flow that depends on the investments to energy saving arrangements and operations. The solution is based on the system dynamics method. The method makes possible to interconnect technical and economic parts of the problem. The main parameter in the model is the energy consumption in the building per floor square meter and year. This parameter is influenced by a deterioration of the building structure and the components of the active elements. Another influence are the investments that are realized with the aim to decrease the energy consumption. The example of the calculation of the main system parameters during the building life cycle with two projects is presented in the paper. The main output from this research is the developed model which makes possible to investigate the influence of multiple energy saving projects during the building life cycle.